Impact of renewable energy sources on relay protection operation; AIP Conference Proceedings; Vol. 2135 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2019) - Andreev M. V. Mikhail Vladimirovich (2019, 2019)
Title screen